(untitled) (Asian Education Studies, 2020)
Learning burnout circumstances appear commonly in the process of English learning. The current research investigates the features of learning burnout of English and a non-English major junior student from three dimensions, including exhaustion, cynicism and decreased professional self-efficacy. Results find that, firstly, these two groups of participants hold a similar degree of learning burnout, while non-English major participants show more individual variability of the learning burnout situation. Based on Krashen’s Input hypothesis and Affective Filter hypothesis, there exist differences and similarities of reasons for participants’ learning burnout. The high degree of learning burnout of these two groups is influenced by the choice of expected jobs as well as the sense of inferiority caused because of peer pressure. Furthermore, learning burnout of English major students is more influenced by teachers, having higher expectations for comprehensible and sufficient input. Therefore, teachers should pay attention to students’ learning burnout situation and understand the specific needs and practical condition of junior students.